ALK-Positive Squamous Cell Carcinoma Dramatically Responded to Alectinib - Ray Sagawa; Takehiko Ohba; Eisaku Ito; Susumu Isogai (Case Reports in Oncological Medicine)
Anaplastic lymphoma kinase (ALK) rearrangement is usually observed in patients with adenocarcinoma. Herein, we report a case of squamous cell carcinoma (SCC) with ALK rearrangement treated with alectinib. The patient was a 73-year-old woman without a smoking history. She consulted us with nonproductive cough and loss of appetite. Computed tomography scan revealed a mass in the left lower lobe of the lung. According to the pathological examinations, we diagnosed the tumor as SCC. Because the patient had never smoked, we searched for driver mutations and found that the tumor harbored ALK rearrangement. We began treatment with alectinib, and the tumor remarkably reduced in volume. No severe adverse events were observed. Although there are only few reports of SCC with ALK rearrangement, this case implies that clinicians should consider searching for driver mutations in patients with SCC when there are atypical findings or characteristics.